The Correlation Analysis between the Number of CIF and the Number of Account at Bank Syariah Indonesia KCP Batam Raden Patah - Rani Gusrita; Nahrul Hayati (JURNAL SINTAK, 2024)
A crucial indicator in assessing the progress and performance of Islamic banks can be seen from the quantity of customers, which is reflected through the number of CIFs (Customer Information Files) and total accounts. This study aims to analyze the correlation between the number of CIFs and the number of accounts at Bank Syariah Indonesia (BSI) Batam Raden Patah Sub-Branch Office. This research uses monthly secondary data from May 2023 to July 2024, covering a period of 15 months. The analytical methods used include descriptive statistics, Kolmogorov-Smirnov normality test, Pearson correlation analysis, and trend analysis. The results show a very strong and significant positive correlation between the number of CIFs and the number of accounts. Trend analysis reveals consistent growth in both variables, with an increase of 8% in the number of CIFs and 7.12% in the number of accounts during the observation period. Keywords: CIF; accounts; Pearson correlation